CACHOEIRA DA MARIQUINHA: IMPACTOS E POTENCIALIDADES DO USO PÚBLICO NO PARQUE NACIONAL DOS CAMPOS GERAIS-PR - Garcia, Lilian Vieira Miranda (2015)
Developing and maintaining a high quality public visitor use program is an effective way of ensuring the appropriate combination of preservation and visitor use in protected areas. Public use is one of the primary objectives in the creation of a park and protected area. This implies that public use must be managed appropriately to minimize potential environmental impacts and improve the quality of the visitor experience. The goals of public use management are to build stewardship of protected areas and to encourage protection of the natural and cultural/heritage resources. This study aims to discuss the public visitation activity at Mariquinha Waterfall, one of the primary tourism areas within the Campos Gerais National Park (CGNP), a conservation unit of the The Chico Mendez Institute (ICMBio). ICMBio is responsible for managing all Brazil National Park units. Campos Gerais National Park was created by ICMBio in 2006, in Paraná, Brazil, to preserve the last remnants of fields and forested settings in the region. Mariquinha Waterfall has been a privately owned tourist destination for decades, but public use impacts on the environment were not at all considered, nor were ecotourism or basic visitor management practices. The Methodological Guide for Management of Visitation Impacts, developed by ICMBio, was the guiding tool that drove the methodology in this study. The Guide was used as a guiding tool to analyze the social impacts and natural resource impacts, to develop a visitor profile and understand tourism activities, to inventory and improve infrastructure, and other management parameters. The Guide and the tourism study (n=118) suggested Mariquinha Waterfall has great potential for outdoor recreation activities within the nature-based tourism resources that exist in the study area. The study showed that the visitors were younger, Ponta Grossa residents who predominately visited in family/family and friends groups, and sought contact with nature. Results of the study also showed there is no direct relationship between the number of visitors and negative impacts, and that impacts be minimized through management actions. Recommendations include monitoring the quality of the visitor experience, as crowding and conflict have the potential to negatively impact visitor experiences. The study then suggested management actions that can minimize social impacts on the environment and strengthen the relationship between visitors and the Park.